Relationship of Medial Meniscus Posterior Root Tears with Proximal Tibial Morphology and Knee Osteoarthritis - Çamur, Eren; Duran, Semra (The Journal of Knee Surgery, 2025)
The meniscus is vital to knee function. Medial meniscus posterior root tear (MMPRT) causes a loss of hoop tension. This, in turn, reduces the meniscus's ability to transmit load. Thus, the higher pressure on the weight-bearing surface speeds up joint degeneration. proximal tibial morphology (PTM) describes the geometric structure of tibia near the knee joint and tibial plateau. Medial posterior tibial slope angle (MPTSA) has the most significant impact on knee biomechanics among PTM measurements. This study aims to investigate the relationship between PTM and MMPRT, and evaluate the association between medial meniscal extrusion amount (MMEA) and osteoarthritis (OA) in patients with MMPRT. This retrospective study analyzed knee magnetic resonance imaging (MRI) of 100 patients with MMPRT and 100 age, gender, side-matched controls. MPTSA, mediolateral length (MLL), medial anteroposterior width (MAW), and lateral anteroposterior width (LAW) were used to evaluate PTM. MMEA and tear gap (TG) correlation and their relationship with knee OA severity was assessed. MPTSA was significantly higher in MMPRT group compared with controls (p < 0.001). Moderate positive correlation was found between MMEA and OA severity (R2 = 0.445, p < 0.001). Cartilage loss was observed when MMEA exceeded 4 mm (sensitivity: 80.68%; specificity: 83.33%). MMEA increased by 1.10 mm for each 1 mm increase in TG. This groundbreaking study reveals that steeper medial tibial plateau is a significant risk factor for MMPRT. Strikingly, MMEA exceeding 4 mm serves as a critical threshold for cartilage loss which is the first finding of OA, potentially revolutionizing treatment decisions. These findings not only enhance our understanding of MMPRT pathomechanics but also provide crucial insights for early intervention strategies, potentially altering the course of OA progression in patients with MMPRT.
Keywords: meniscus; root tear; morphology; osteoarthritis; knee